2021
DOI: 10.1021/acs.est.1c01512
|View full text |Cite
|
Sign up to set email alerts
|

Weathering Plastics as a Planetary Boundary Threat: Exposure, Fate, and Hazards

Abstract: We described in 2017 how weathering plastic litter in the marine environment fulfils two of three criteria to impose a planetary boundary threat related to "chemical pollution and the release of novel entities": (1) planetary-scale exposure, which (2) is not readily reversible. Whether marine plastics meet the third criterion, (3) eliciting a disruptive impact on vital earth system processes, was uncertain. Since then, several important discoveries have been made to motivate a re-evaluation. A key issue is if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(101 citation statements)
references
References 115 publications
0
101
0
Order By: Relevance
“…Similar to other plastic items, once medical masks are disposed of into the natural environment, they undergo weathering processes, including ultraviolet radiation, temperature fluctuations, increased humidity, biodegradation, physical abrasion and chemical oxidation. Weathering affects the physicochemical properties of plastics, and eventually leads to their fragmentation into microplastics and nanoplastics [ 15 19 ]. The degradation of plastics is highly dependent on the polymer type and any chemical additives [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other plastic items, once medical masks are disposed of into the natural environment, they undergo weathering processes, including ultraviolet radiation, temperature fluctuations, increased humidity, biodegradation, physical abrasion and chemical oxidation. Weathering affects the physicochemical properties of plastics, and eventually leads to their fragmentation into microplastics and nanoplastics [ 15 19 ]. The degradation of plastics is highly dependent on the polymer type and any chemical additives [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“… Sarker et al (2020) observed that long-term environmental weathering reduced the toxicity of a high-density PE bag and PVC matting towards a marine microbe. A comparatively lower hazard can result from aged plastics taken from the environment because the release of chemicals already occurs during the aquatic lifetime ( Gardon et al, 2020 ; Arp et al, 2021 ). In contrast, Luo et al (2020) has shown that aged MPs (<500 µm PE that includes chrome yellow) caused an inhibition in algal cells because a comparably higher amount of chromium and lead was released.…”
Section: Discussionmentioning
confidence: 99%
“…As already described by Bridson et al (2021) and discussed here, the adverse effects of plastic leachates are not under debate. However, the extent to which hazardous chemicals are released due to weathering and affect aquatic organisms is of specific concern ( Arp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations